Soft X-Ray Spectroscopy of Low-Valence Nickelates - Hepting, Matthias; Dean, Mark P. M.; Lee, Wei-Sheng (Frontiers in Physics, 2021)
Low-valence nickelates — including infinite-layer (IL) and trilayer (TL) compounds — are longstanding candidates for mimicking the high-temperature superconductivity of cuprates. A recent breakthrough in the field came with the discovery of superconductivity in hole-doped IL nickelates. Yet, the degree of similarity between low-valence nickelates and cuprates is the subject of a profound debate for which soft x-ray spectroscopy experiments at the Ni L- and O K-edge provided critical input. In this review, we will discuss the essential elements of the electronic structure of low-valance nickelates revealed by x-ray absorption spectroscopy (XAS) and resonant inelastic x-ray scattering (RIXS). Furthermore, we will review magnetic excitations observed in the RIXS spectra of IL and TL nickelates, which exhibit characteristics that are partly reminiscent of those of cuprates.